A surface acoustic wave-driven micropump for particle uptake investigation under physiological flow conditions in very small volumes - Strobl, Florian G.; Breyer, Dominik; Link, Phillip; Torrano, Adriano A.; Bräuchle, Christoph; Schneider, Matthias F.; Wixforth, Achim (Beilstein Journal of Nanotechnology, 2015)
Static conditions represent an important shortcoming of many in vitro experiments on the cellular uptake of nanoparticles. Here, we present a versatile microfluidic device based on acoustic streaming induced by surface acoustic waves (SAWs). The device offers a convenient method for introducing fluid motion in standard cell culture chambers and for mimicking capillary blood flow. We show that shear rates over the whole physiological range in sample volumes as small as 200 μL can be achieved. A precise characterization method for the induced flow profile is presented and the influence of flow on the uptake of Pt-decorated CeO2 particles by endothelial cells (HMEC-1) is demonstrated. Under physiological flow conditions the particle uptake rates for this system are significantly lower than at low shear conditions. This underlines the vital importance of the fluidic environment for cellular uptake mechanisms.
Keywords: acoustic streaming; cellular uptake; flow; nanoparticles; sedimentation; shear; surface acoustic wave (SAW)